2016
DOI: 10.3389/fpls.2016.01314
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Studies on the Effects of Lipo-Chitooligosaccharide and Thuricin 17 under Unstressed and Salt Stressed Conditions in Arabidopsis thaliana

Abstract: Plants, being sessile organisms, are exposed to widely varying environmental conditions throughout their life cycle. Compatible plant-microbe interactions favor plant growth and development, and help plants deal with these environmental challenges. Microorganisms produce a diverse range of elicitor molecules to establish symbiotic relationships with the plants they associate with, in a given ecological niche. Lipo-chitooligosaccharide (LCO) and Thuricin 17 (Th17) are two such compounds shown to positively infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 78 publications
1
50
0
1
Order By: Relevance
“…Understanding naturally occurring PGPR beneficial features and interactions could foster the design of agro-systems with decreased fertilizer inputs and sustained or improved plant yields. The most widely explored plant beneficial trait is the mutual symbiotic biological nitrogen fixation by Rhizobia (Udvardi and Poole 2013), but numerous other nutrient acquisition Subramanian et al 2016 *The role of PGPR SA production in plant defense is debated machineries have been observed which facilitate plant access to macro-nutrients, micro-nutrients, and carbon allocation.…”
Section: Bacteria Enhance Plant Nutrient Acquisition and Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding naturally occurring PGPR beneficial features and interactions could foster the design of agro-systems with decreased fertilizer inputs and sustained or improved plant yields. The most widely explored plant beneficial trait is the mutual symbiotic biological nitrogen fixation by Rhizobia (Udvardi and Poole 2013), but numerous other nutrient acquisition Subramanian et al 2016 *The role of PGPR SA production in plant defense is debated machineries have been observed which facilitate plant access to macro-nutrients, micro-nutrients, and carbon allocation.…”
Section: Bacteria Enhance Plant Nutrient Acquisition and Growthmentioning
confidence: 99%
“…HMB (Fatima and Anjum 2017). The bacteriocin peptide Thuricin 17 (Th17) from the PGPR Bacillus thuringiensis strain NEB17, has long been known to have antimicrobial activities (Gray et al 2006), but recent proteomic analysis of salt-stress Arabidopsis suggests that it may alleviate the deleterious effect of the abiotic stress on photosystems I and II through upregulation of chloroplast proteins (Subramanian et al 2016).…”
Section: Diverse Pgpr Molecules Elicit Plant Defensementioning
confidence: 99%
See 2 more Smart Citations
“…These include bacteria in the soil near plant roots, on the surface of plant root systems, in spaces between root cells or inside specialized cells of root nodules; they stimulate plant growth through a wide range of mechanisms ( Gray and Smith, 2005 ; Mabood et al, 2014 ), such as: (1) nutrient solubilization (particularly phosphorus – Boddey et al, 2003 ; Kennedy et al, 2004 ; Trabelsi and Mhamdi, 2013 ), (2) production of metal chelating siderophores, (3) nitrogen fixation ( Vessey, 2003 ; Bhattacharyya and Jha, 2012 ; Drogue et al, 2012 ), (4) production of phytohormones, (5) production of 1-aminocyclopropane-1-carboxylate deaminase, (6) production of volatile organic compounds, (7) induction of systemic resistance [induced systemic resistance (ISR) and systemic required resistance (SAR) – Jung et al, 2008b , 2011 ], and (8) suppression of disease through antibiosis ( Bhattacharyya and Jha, 2012 ; Spence et al, 2014 ). It has also been shown that “signal” compounds produced by bacteria in the phytomicrobiome stimulate plant growth ( Prithiviraj et al, 2003 ; Mabood et al, 2006a ; Lee et al, 2009 ), particularly in the presence of abiotic stress ( Wang et al, 2012 ; Subramanian, 2014 ; Prudent et al, 2015 ). In the broadest sense PGPR include legume-nodulating rhizobia.…”
Section: The Phytomicrobiome and Plant Growthmentioning
confidence: 99%